Imagining Disability Futurities. (2017) - Rice, Carla; Chandler, Eliza; Rinaldi, Jen; Changfoot, Nadine; Liddiard, Kirsty; Mykitiuk, Roxanne; Mündel, Ingrid
Abstract : This article explores twelve short narrative films created by women and trans people living with disabilities and embodied differences. Produced through Project ReVision, these micro documentaries uncover the cultures and temporalities of bodies of difference by foregrounding themes of multiple histories: body, disability, maternal, medical, and/or scientific histories; and divergent futurities: contradictory, surprising, unpredictable, opaque, and/or generative futures. We engage with Alison Kafer's call to theorize disability futurity by wrestling with the ways in which "the future" is normatively deployed in the service of able‐bodiedness and able‐mindedness (Kafer 2013 ), a deployment used to render bodies of difference as sites of "no future" (Edelman 2004 ). By re‐storying embodied difference, the storytellers illuminate ongoing processes of remaking their bodily selves in ways that respond to the past and provide possibilities for different futures; these orientations may be configured as "dis‐topias" based not on progress, but on new pathways for living, uncovered not through evoking the familiar imaginaries of curing, eliminating, or overcoming disability, but through incorporating experiences of embodied difference into time. These temporalities gesture toward new kinds of futures, giving us glimpses of ways of cripping time, of cripping ways of being/becoming in time, and of radically re‐presencing disability in futurity.